Konseling Traumatik Untuk Menangani Gangguan Kesehatan Mental Trauma Pada Korban Pelecehan Seksual - Ning Sasi Awaliyah; Ulin Nihayah; Khozaainatul Muna (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2021)
The purpose of this study is to see the effect of a person's mental health which is influenced by events in life that have a major impact on a person's personality and behavior. These events can include catching up in the household, children, or long term. The literature study combines the study of the literature found by the authors. The results showed; 1) The victim is very traumatized by the sexual incident and must be accompanied by a counselor for his decision. 2) handling of victims, with several conditions experienced by victims after treatment, including; a) feel relieved and already want to talk to other people and family b). feel have the spirit of life c). His condition is more stable because he feels comfortable after receiving therapy from a counselor.